20. yüzyıl sanatında teknolojinin yeri - Çiçekli, Pınar (My University, 2008)
The Position of Technology in 20. Century Art The aim in analysing 20. century art and artistic structures paralleling science and technology is; associating art, technology and societyconsidering and going through the influence of technology on living spaces, the functionality of machines and technical products going into pieces of art, the effects on art by means of methods and material, reproduction becoming mass production, the active and passive role of art in techno-art relations, variance of essence and form inspired by technology. Refusing to be indifferent to the developments and innovations of their time, the modern artists used technologic fact in their works and this provoked art to obtain a new identity, use expressive tools and reform in a new structure. Time and labor savings that technology provides in practical lkife and the facts of fastness, action and dynamism that it adds to the whole of life have been reflected on works of art by use of technical objects or by creation of the impression of fast and active through formality. Art, which can be defined as a language, as a form of expression, has increased its opportunities of communication, has expanded its domain of formal expression by means of several materials provided by technology and, through its structural modification, it has passed to the dimension of concept in this century. Apart from the structuring in terms of form and content, 20th century artists evaluated the effects of technology on individual's and society's life by positive and negative characterizations. These evaluations are made on such subjects as the popular culture emerging, the imbalance between production and consumption as a consequence of industrialisation, existence and use of mass destruction weapons, increasing isolation of the individual wihin a world that is getting crowded, progress in the communication and information networks, and effects of mechanical and electronic art formations. While the technological and artistic developments of the 20th century are assessed, since it sheds a light upon the developments of 20th century, the 19th century is also included by taking the important reflections of the industrial revolution. Written and visual resources have been surveyed, translation has been made from various languages, and the Internet has been made use of. Paintings thought to constitute examples that shed a light on the relation between technology and art has been provided as examples.. Technology, technique, art, object, technic object, art object.

20. Yüzyıl Sanatında Teknolojinin Yeri 20. yüzyıl sanatının, sanat oluşumlarının bilim ve teknoloji paralelinde incelenmesiyle; teknolojinin yaşam alanlarına nüfuz edişi, makinelerin işlevselliği ve teknik ürünlerin sanat eserlerine dâhil oluşu, sanata teknik ve malzeme açısından etkileri, yeniden üretimin çoğaltıma dönüşmesi, sanat- teknoloji ilişkisinde sanatın etken ve edilgen rolü, teknolojiden etkilenme ile öz ve biçim dengesindeki değişiklikler, sanat-teknoloji ve toplum üçgeninin ilişkilendirilmesi amaçlanmıştır. Yaşadığı zamanın gelişmelerine, yeniliklerine kayıtsız kalmayan çağdaş sanatçıların eserlerine taşıdıkları teknoloji olgusu, sanatın yeni kimlikler edinmesine, ifade araçları kullanmasına ve yapısal değişikliklere uğramasına neden olmuştur. Teknolojinin yaşamın pratiğine kazandırdığı zaman- emek tasarrufu ve yaşamın bütününe kattığı hız- hareket- dinamizm olguları, sanat eserlerinde teknik nesnelerin kullanımıyla veya tuval düzleminde biçimsellikle ‘hızlı ve hareketli’ izlenimi yaratmasıyla aktarılmıştır. Bir dil, bir ifade biçimi olarakta tanımlanabilen sanat, bu yüzyılda iletişim olanaklarını arttırmış, teknolojinin sunmuş olduğu birçok malzeme ile biçimsel anlatım alanını genişletmiş, yapısal değişikliği ile kavram boyutuna geçmiştir. 20. yüzyıl sanatçıları, biçim ve içerik bakımından yapılanmanın yanı sıra, teknolojinin birey ve toplum yaşantısına etkilerini de olumlu ve olumsuz nitelemelerle değerlendirmiştir. Bu değerlendirmeler, oluşan popüler kültür, sanayileşmenin sonucu olan üretim- tüketim dengesizliği, kitle imha araçlarının varlığı ve kullanımı, kalabalıklaşan dünyada bireyin yalnızlaşması, iletişim ve bilgilenim ağının ilerlemesi, mekanik ve elektronik sanat oluşumlarının etkileri gibi konular üzerinedir. 20. yüzyıldaki teknolojik ve sanatsal gelişmeler ele alınmakla birlikte, 19. yüzyıl da, 20. yüzyıl gelişmelerine ışık tutması nedeniyle, özellikle sanayi devriminin önemli yansımalarının dikkate alınmasıyla konunun kapsamına dâhil edilmiştir. Yazılı ve görsel kaynaklar taranmış, çeşitli dillerden çeviriler yapılmış, internet ortamından yararlanılmıştır. Teknoloji- sanat ilişkisine ışık tutabileceği düşünülen resimlere örnek teşkil etmesi için yer verilmiştir. Anahtar Sözcükler: Teknoloji, teknik, sanat, nesne, teknik nesne, sanatsal nesne.
Keywords: Sanat_Teknoloji